Towards rapid large-scale LIPSS fabrication by 4-beam ps DLIP. (January 2021) - Hauschwitz, P.; Jochcová, D.; Jagdheesh, R.; Rostohar, D.; Brajer, J.; Kopeček, J.; Cimrman, M.; Smrž, M.; Mocek, T.; Lucianetti, Antonio
Graphical abstract: Highlights: Interference area is increased up to 1 mm in diameter to reach higher throughputs. Parameters for fabrication of LIPSS-structured microcraters are investigated. Throughputs up to 30 400 LSFL spots/s and 203 200 HSFL spots/s are achieved. Superhydrophobicity and structural colours are demonstrated on selected surfaces. Abstract: Using four beam direct laser interference patterning (DLIP) Laser Induced Periodic Surface Structures (LIPSS, ripples) are simultaneously generated on surface of AISI 316L steel in more than thousands of spots at once. Both low-spatial frequency LIPSS (LSFL) and high-spatial frequency LIPSS (HFSL) are possible to fabricate with optimized parameters of 1030 nm, 1.7 ps PERLA laser system, developed and operated at HiLASE center. A novel large-beam DLIP technique applied for the redistribution of initial laser energy per pulse results in fabrication of 1520 spots with LSFL in 50 ms and 1016 spots with HSFL in 5 ms, thus significantly improving the productivity in comparison with the single beam approach. Efficient production of LIPSS structures over large area, required for applications such as a production of security diffractive elements and surfaces with superhydrophobic properties is also demonstrated. Possible steps for further increase of processing speed are discussed.